A pilot study of occupational exposure to ultrafine particles during 3D printing in research laboratories - Felici, Giorgio; Lachowicz, Joanna Izabela; Milia, Simone; Cannizzaro, Emanuele; Cirrincione, Luigi; Congiu, Terenzio; Jaremko, Mariusz; Campagna, Marcello; Lecca, Luigi Isaia (Frontiers in Public Health, 2023)
3D printing is increasingly present in research environments, and could pose health risks to users due to air pollution and particulate emissions. We evaluated the nanoparticulate emissions of two different 3D printers, utilizing either fused filament fabrication with polylactic acid, or stereolithography (SLA) with light-curing resin. Nanoparticulate emissions were evaluated in two different research environments, both by environmental measurements in the laboratory and by personal sampling. The SLA printer had higher nanoparticulate emissions, with an average concentration of 4091 parts/cm3, versus 2203 particles/cm3 for the fused filament fabrication printer. The collected particulate matter had variable morphology and elemental composition based on carbon, sulfur and oxygen, the main combustion products. Our study implies that when considering the health risks of particulate emissions from 3D printing in research laboratories, attention should be given to the materials used and the type of 3D printer.